Portable Residential Power Monitoring Distribution Box - MUHAMMAD SYABIL HAZIQ ZAIDI; OMAR ABU HASSAN (Progress in Engineering Application and Technology, 2025)
The increasing adoption of renewable energy and rising electricity costs have heightened the need for affordable, user-friendly power monitoring solutions for residential consumers. Conventional power monitoring systems are often large, expensive, and devoid of remote accessibility and real-time data logging. The Internet of Things (IoT) is used in this project to provide a portable residential power monitoring distribution box with notification capability that fills these gaps by accurately monitoring power use. A NodeMCU ESP32 microcontroller, SCT-013 current transformers, and a ZMPT101B AC voltage sensor are all integrated into the suggested system to measure electrical parameters in real time. A DS1307 data-logger shield is also included in the system to timestamp and locally record power data. Users may monitor their household's power use, trends in energy usage, and receive alerts of unusual usage on their smartphones thanks to these readings, which are instantly relayed over Wi-Fi to the Blynk application and shown on an LCD screen for instant feedback. The device's ability to measure current and voltage correctly within reasonable tolerances was shown during testing under various load circumstances. The system's dependability was confirmed by the small discrepancy between measured data and multimeter readings. Additionally, data was successfully sent and shown on the Blynk dashboard for both historical and real-time analysis. To sum up, home users may monitor power consumption, effectively regulate energy usage, and promote energy conservation with this portable monitoring box. This system may be expanded to monitor three-phase electricity in the future, and machine learning can be used to add predictive features for better energy management